Sistem Monitoring Kolam Bioflok Bagi Petani Ikan Nila di Pulau Batam - Pamungkas, Daniel Sutopo; Aryeni, Illa; K L N Suciningtias, Ika; Y D Salwa, Rafiqah; R Pangestu, Urip; E Samosir, Precelia; Hasanuddin, Mohammad; S Sirait , Eha (Journal of Applied Community Engagement, 2025)
This project aims to develop an Internet of Things (IoT)--based water quality monitoring system specifically designed for optimizing tilapia cultivation. This system utilizes electronic sensors to monitor Total Dissolved Solids (TDS) parameters, pH, temperature, and dissolved oxygen (DO). The data obtained is processed by an ESP32 microcontroller and displayed in real time on an LCD screen, making it easier for farmers to monitor water conditions. An additional feature in the form of a buzzer alarm provides an early warning if the water quality parameters are outside the safe threshold. With this system, farmers can quickly take corrective action, minimize the risk of fish mortality, and increase resource use efficiency. The system implementation results are expected to support economic and environmental sustainability in tilapia cultivation.